Left Atrial Appendage (LAA) Function by Transesophageal Echocardiography before and after Percutaneous Balloon Mitral Valvuloplasty (PBMV)- A Comparative Study (Academia Journal of Medicine, 2020)
Background: In the past, the left atrial appendage (LAA) has been considered to be a relatively insignificant portion of cardiac anatomy. It is now recognized that it is a structure with important pathological associations. First, thrombus has a predilection to form within the LAA in patients with non-valvar atrial fibrillation and to a lesser extent in those with mitral valve disease (both in atrial fibrillation and in sinus rhythm). Second, the use of transoesophageal echocardiography has made clear imaging of the LAA possible, so that its size, shape, flow pattern, and content can be assessed in health and disease. Subjects and Methods: This study population consisted of 40 patients with symptomatic mitral stenosis who underwent percutaneous mitral balloon valvotomy in the cardiology department of GSL medical college, Rajahmundry over a time period of 1 April 2017 to 30 March2018. Patients in all age groups, with evidence of severe MS (MVA
Keywords: Rheumatic Mitral Stenosis; Left Atrial Thrombus; Thromboembolism; Transesophageal Echocardiography